The Running Record as Method to Improve The students' Reading Ability - Sukarwati, Nasrah; Akib, Erwin; Setiadi, Muhammad Astrianto (English Language Teaching Methodology, 2023)
The purpose of this study was to determine whether the used of running records as a learning method could improved students' reading skills at Mts Muhammadiyah Likuboddong. The research method used was the pre-experiment method with one group pretest and posttest design. The researcher collected data by gave  pretest and posttest by gave essay test. The subjects of this study were 2nd grade students of Mts Muhammadiyah Likuboddong. Sampling used total sampling. The total of samples was 18 students.The results showed that the used of running records as a learning method could improved students' reading skills. This was evidenced by the average value of the main idea in the pre test was 44.9 which increased in the posttest to 65.2 with an increased of 45%. While the average value of supporting ideas in the pretest was 40.6, increased in the posttest to 58.8 with an increased of 44%. This means that there was an increased in students' reading ability, especially in literal understanding related to main ideas and supporting ideas and it was concluded that running records as a learning method can improved students' reading skills at Mts Muhammadiyah Likuboddong. Thus it was stated that the Null Hypothesis (H0) was rejected and the alternative hypothesis (H1) was accepted.